The Influence of Information Technologies and Production Processes in the Decisions of Human Resources Personnel at the Organizational Level in Times of COVID-19 - Díaz-Martínez, Marco Antonio (2023)
The purpose of this investigation is to conduct an analysis of the influence of information technologies (ICTs) and production processes in organizations in the industrial sector in the state of Tamaulipas during times of COVID-19. The study evaluated the municipalities of Tampico, Altamira and Reynosa. The research instrument was applied to managers and directors of different organizations, producing a total of 45 interviews and employing the partial least squares (PLS) regression technique for data analysis. The Omega McDonald index and Dillon-Goldstein’s RHO were employed to assess the instrument’s confidence level. The results indicate that the intervention new information technologies (ICTs) as tools for innovation and competitiveness in the labor market contributed as much as nearly 84 %.